Nuclear corepressor SMRT acts as a strong regulator of both β-oxidation and suppressor of fibrosis in the differentiation process of mouse skeletal muscle cells. - Hiroaki Shimizu; Yasuhiro Horibata; Izuki Amano; Megan J Ritter; Mariko Domae; Hiromi Ando; Hiroyuki Sugimoto; Ronald N Cohen; Anthony N Hollenberg (PLoS ONE)
Background Silencing Mediator of Retinoid and Thyroid hormone receptors (SMRT; NCoR2) is a transcriptional corepressor (CoR) which has been recognized as an important player in the regulation of hepatic lipogenesis and in somatic development in mouse embryo. SMRT protein is also widely expressed in mouse connective tissues, for example adipocytes and muscle. We recently reported that mice with global deletion of SMRT develop significant obesity and muscle wasting which are independent from thyroid hormone (TH) signaling and thermogenesis. However, the tissue specific role of SMRT in skeletal muscle is still not clear. Methods To clarify role of SMRT in muscle differentiation, we made myogenic C2C12 clones which lack SMRT protein (C2C12-SKO) by using CRISPR-Cas9. Wild-type C2C12 (C2C12-WT) and C2C12-SKO cells were cultured in differentiation medium, and the resulting gene and protein profiles were compared between the two cell lines both before and after differentiation. We also analyzed muscle tissues which were dissected from whole body SMRT knockout (KO) mice and their controls. Results We found significant up-regulation of muscle specific β-oxidation markers; Peroxisome proliferator-activated receptor δ (PPARδ) and PPARγ coactivator-1α (PGC-1α) in the C2C12-SKO cells, suggesting that the cells had a similar gene profile to what is found in exercised rodent skeletal muscle. On the other hand, confocal microscopic analysis showed the significant loss of myotubes in C2C12-SKO cells similar to the morphology found in immature myoblasts. Proteomics analysis also confirmed that the C2C12-SKO cells had higher expression of markers of fibrosis (ex. Collagen1A1; COL1A1 and Fibroblast growth factor-2; FGF-2), indicating the up-regulation of Transforming growth factor-β (TGF-β) receptor signaling. Consistent with this, treatment with a specific TGF-β receptor inhibitor ameliorated both the defects in myotube differentiation and fibrosis. Conclusion Taken together, we demonstrate that SMRT functions as a pivotal transcriptional mediator for both β-oxidation and the prevention for the fibrosis via TGF-β receptor signaling in the differentiation of C2C12 myoblasts. In contrast to the results from C2C12 cells, SMRT does not appear to play a role in adult skeletal muscle of whole body SMRT KO mice. Thus, SMRT plays a significant role in the differentiation of myoblasts.